2017
DOI: 10.1038/bjc.2017.99
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis comparing the risk of metastases in patients with rectal cancer and MRI-detected extramural vascular invasion (mrEMVI) vs mrEMVI-negative cases

Abstract: Background:Pathological extramural vascular invasion (EMVI) is an independent prognostic factor in rectal cancer, but can also be identified on MRI-detected extramural vascular invasion (mrEMVI). We perform a meta-analysis to determine the risk of metastatic disease at presentation and after surgery in mrEMVI-positive patients compared with negative tumours.Methods:Electronic databases were searched from January 1980 to March 2016. Conventional meta-analytical techniques were used to provide a summative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 43 publications
(95 reference statements)
8
75
2
Order By: Relevance
“…This is concordant with previous studies that found mrEMVI to be associated with poor prognosis. In a large meta‐analysis including 1262 patients, those with mrEMVI developed metastases more frequently than those with mrEMVI‐negative tumours (odds ratio 5·68; P < 0·001). These findings highlight the critical role of mrEMVI evaluation in patient stratification.…”
Section: Discussionsupporting
confidence: 90%
“…This is concordant with previous studies that found mrEMVI to be associated with poor prognosis. In a large meta‐analysis including 1262 patients, those with mrEMVI developed metastases more frequently than those with mrEMVI‐negative tumours (odds ratio 5·68; P < 0·001). These findings highlight the critical role of mrEMVI evaluation in patient stratification.…”
Section: Discussionsupporting
confidence: 90%
“…52 EMVI status may also be a poor prognostic factor for metastases, as a recent meta-analysis reported mrEMVI positive patients presented five times more frequently with synchronous metastases and developed metastases four times more often after curative resection than mrEMVI negative tumors. 53 The combination of MRI assessment of EMVI, a 1-mm or less distance from the tumor to the surgical resection plane, and the mrTRG in patients after nCRT may be more powerful prognostic predictors than T and N stages. 31 With these signs, MRI provides invaluable prognostic information, and is an essential part of the staging for the MDT to make appropriate treatment decisions.…”
Section: Using High-resolution Mri To Determine Prognosis and Predictmentioning
confidence: 98%
“…These deposits are strong adverse prognostic determinants, and there is a relation between extramural extranodal tumor deposits and extramural venous invasion [89,90]. Lymphovascular involvement which is tumor invasion into veins, especially extramural veins, or lymphatics is thought to be an adverse prognostic factor [91][92][93]. Perineural invasion is also associated with an elevated risk of recurrence and poor prognosis [94,95].…”
Section: Prognosismentioning
confidence: 99%